Optimalisasi Pembelajaran Irama Qiro’ah Melalui Metode Demonstrasi Dalam Ektrakurikuler - Mega Dwi Susanti; Dina Farihatun Nisa’ (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research was conducted because the students' ability to apply the rhythm of qiro'ah at SDI Sabilil Huda is still low, with only 35% of students able to read the Qur'an with good and correct rhythm. This study aims to improve students' qiro'ah rhythm skills through the application of demonstration methods in extracurricular activities. This study uses a Classroom Action Research (CAR) method consisting of two cycles. The research subjects were 20 students participating in qiro'ah extracurricular activities. Each cycle in this study includes four stages, namely planning, implementation, observation, and reflection. Data collection techniques in this study included observation, practice tests, and interviews. The results showed a significant increase in students' qiro'ah rhythm skills after the action was taken. In the first cycle, the success rate of students reached 60% with an average class score of 72.8. Then, in the second cycle, the success rate increased to 85% with an average class score of 83.6. This increase was also seen from the increase in students' self-confidence and their active participation in the learning process. In conclusion, the implementation of demonstration methods in extracurricular activities proved effective in optimizing qiro'ah rhythm learning at SD Sabilil Huda.